EVALUASI KAPASITAS STRUKTUR GEDUNG MEOTEL BY DAFAM JEMBER DENGAN METODE PUSHOVER ANALYSIS - Wardhani, Ajeng Safira Kusuma; Priyono, Pujo; Manggala, Adhitiya Surya (HEXAGON, 2019)
The territory of Indonesia, including areas prone to disasters, especially geological natural disasters, is caused by Indonesia's position located at the confluence of 3 (three) world tectonic plates. One of the geological natural disasters that often occurs in Indonesia is an earthquake. The Meotel by Dafam Jember building deserves to be analyzed by the pushover analysis method because it is a multi-storey building that is 10 floors so it must have earthquakeresistance as tectonic activity increases in Indonesia. The study was conducted with the help of SAP2000 v.20 software. Through the ATC-40 curve, the target value of the displacement target and the base shear force in the X direction at the control point of the performance point in the modelling are displacements of 0.075 m and the base shear of 7338.716 kN. The value of the roof drift ratio X direction of 0.1928% is included in the Immediate Occupancy category. The results of the pushover analysis on the structure of Meotel by Dafam Jember show the performance of the building at the level of Immediate Occupancy (IO).